Application of Project Management Model with Theory of Constraints to Minimize Project Completion Time and Direct Labor Costs - Wahyudin, Cucu; Sukwadi, Ronald; Rahmawati, Sinta Rahmawati (Metris: Jurnal Sains dan Teknologi, 2025)
Small and medium-scale manufacturing industries generally face difficulties in minimizing their operational costs. The company's Make-to-Order strategy causes fluctuations in the number of jobs received, so it minimizes fixed costs such as labor wages. This phenomenon occurs in rectifier panel manufacturing companies and various other companies. Companies minimize the number of permanent employees and recruit daily contract employees. Unfortunately, daily contract employees are recruited when orders are received (t=0) so that employees are still paid even though work is not yet available. This study attempts to determine the timing of recruiting daily contract employees that is adjusted to the scheduled work. The method used is a combination of project management with the theory of constraints. The study focuses on three things, namely: (1) Determining the number of workers based on the workload in each position. (2) Conducting project scheduling using the PDM (Precedence Diagram Method) project scheduling method. (3) Applying the Theory of Constraint (TOC) method at problematic workstations so that product flow is balanced. The results of the study show efficient performance, namely: the number of workers decreased from 24 people to 17 people, and the duration of the project decreased from 171 working days to 94 working days